Formulasi Dan Uji Stabilitas Sediaan Krim Tabir Surya Dari Ekstrak Teh Hijau (Camellia Sinensis) - Simanjuntak, Glory Gelarich; Pramono, Edi (Barongko: Jurnal Ilmu Kesehatan, 2025)
Excessive exposure to ultraviolet (UV) light can cause various skin problems, such as premature aging, hyperpigmentation, erythema, and even skin cancer. The use of sunscreen is a primary preventative measure to reduce these risks. However, most commercial sunscreen products contain synthetic chemicals that can cause irritation or other side effects on sensitive skin. Therefore, a safer and more environmentally friendly natural-based sunscreen preparation is needed. This study aimed to formulate a sunscreen cream based on green tea (Camellia sinensis) extract and evaluate its physical stability and effectiveness in absorbing UV light. Green tea extract was obtained through a maceration method using 70% ethanol, then formulated into a cream preparation with varying concentrations of 5%, 10%, and 15%. The evaluation included organoleptic tests, pH, homogeneity, viscosity, spreadability, temperature stability, and in vitro Sun Protection Factor (SPF) calculation using UV-Vis spectrophotometry. The results showed that all formulas exhibited fairly good physical stability during storage. The formula with a 10% extract concentration showed the most optimal results, with an SPF of 13.2, which is categorized as moderate protection, and good physical stability. This study concludes that green tea extract has potential as a natural active ingredient in sunscreen preparations, especially at a concentration of 10%.